Derivation and Culture of Enriched Phrenic-Like Motor Neurons From Human iPSCs - Louise Thiry; Julien Sirois; Thomas Durcan; Stefano Stifani (Bio-Protocol, 2025)
The fatal motor neuron (MN) disease amyotrophic lateral sclerosis (ALS) is characterized by progressive degeneration of the phrenic MNs (phMNs) controlling the activity of the diaphragm, leading to death by respiratory failure. Human experimental models to study phMNs are lacking, hindering the understanding of the mechanisms of phMN degeneration in ALS. Here, we describe a protocol to derive phrenic-like MNs from human induced pluripotent stem cells (hiPSC-phMNs) within 30 days. During spinal cord development, phMNs emerge from specific MN progenitors located in the dorsalmost MN progenitor (pMN) domain at cervical levels, under the control of a ventral-to-dorsal gradient of Sonic hedgehog (SHH) signaling and a rostro-caudal gradient of retinoic acid (RA). The method presented here uses optimized concentrations of RA and the SHH agonist purmorphamine, followed by fluorescence-activated cell sorting (FACS) of the resulting MN progenitor cells (MNPCs) based on a cell-surface protein (IGDCC3) enriched in hiPSC-phMNs. The resulting cultures are highly enriched in MNs expressing typical phMN markers. This protocol enables the generation of hiPSC-phMNs and is highly reproducible using several hiPSC lines, offering a disease-relevant system to study mechanisms of respiratory MN dysfunction. While the protocol has been validated in the context of ALS research, it can be adopted to study human phrenic MNs in other research fields where these neurons are of interest.